Reconfigurable Soft Robots by Building Blocks (Adv. Sci. 33/2022). Issue 33 (24th November 2022) - Atia, Mohamed G. B.; Mohammad, Abdelkhalick; Gameros, Andres; Axinte, Dragos; Wright, Iain
Abstract : Reconfigurable Soft Robots In article number 2203217, Mohamed G. B. Atia, Abdelkhalick Mohammad, and co‐workers present a novel concept of soft building blocks that can be assembled and reconfigured to build different modular configurations of soft robots such as robotic fingers and continuum robots. To validate this approach, three case studies of bio‐inspired designs are demonstrated (2D soft fingers, a legged robot and a 3D robotic elephant trunk).